The Impact of Digital Public Service Innovation on Public Satisfaction at the Jambi City Population and Civil Registration Service in 2024 - Amanah, Dedek; Mukhlis, Maulana (PT. Anagata Sembagi Education, 2025)
This study aims to dissect in more depth the extent to which digital service innovations truly impact citizen satisfaction at the Jambi City Population and Civil Registration Office throughout 2024. Using a quantitative descriptive correlational design, I collected data from 56 respondents using a purposive sampling technique. All input from the Likert-scale questionnaire was then tested in stages using SPSS 25, starting with cross-checking validity and then proceeding to a simple linear regression analysis to precisely map the relationship patterns. The field results provide a fairly convincing picture: digital innovation has been proven to have a positive and significant impact with a contribution (determination coefficient) of 67.7%. Looking at the regression equation Y = 0.847 + 0.759X, a clear mathematical correlation is apparent: for every unit of digital innovation, citizen satisfaction will increase by 0.759 units. This figure confirms that information technology plays a fundamental role, not just a complementary bureaucratic accessory in Jambi. Digital innovation has transformed into a fundamental driving force that dictates the rise and fall of public satisfaction in administrative matters. Another interesting fact is that ease of access emerged as the highest dimension, scoring 4.12, while system reliability was the primary factor contributing to satisfaction, scoring 3.92. Of course, this digitalization path hasn't been smooth sailing, with obstacles such as the digital literacy gap, uneven infrastructure, and frequent system technical glitches hampering progress. Therefore, this study emphasizes the importance of boosting digital education, optimizing infrastructure, and continuously training employees to ensure the quality of public services in Jambi in the future.